Lecturers’ Speech Acts Pattern Viewed from Gender Perspective - Nusi, Ahmad; Yelliza, Yelliza (Jurnal Kreatif Online, 2020)
Language is clearly to occupy a function whereas a number of people are not familiar with the function. In fact, the problem frequently happens in verbal communication in classroom when the utterances cannot be merely interpreted literally since sometimes what lecturers mean is different from what they have been stated. In order to anticipate and minimize the misunderstanding of language function uttered both man and woman lecturers, the model of speech acts is strongly required to be formed related to the gender perspective as the purpose of the research.  Researcher conducted descriptive research with pragmatic identity method with purposive sampling. The data of this research were the English lecturers’ utterances used when communicating with the students in the classrooms. The results of the research were QEC (Questioning, Explaining, Commanding) pattern frequently uttered by woman (16 categories with total 301) and CQE (Commanding, Questioning, Explaining) pattern mostly performed by the man lecturer (8 categories with total 80. In conclusion both of the speech acts models/patterns used in teaching are properly qualified to be implemented since the teaching strategy focuses on students’ center